Assessment Of Gingival Phenotype At The Aesthetic Zone In A Malay Population Using Probe Test - Munirah Yaacob; Muhammad Azat Awang@Semail; Abdul Shukur Mustafa; Juzaily Husain; Noorhazayti Ab. Halim (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: The gingival phenotype (GP) of teeth at the aesthetic zone often influences dental rehabilitation plans and treatment outcomes. This study aimed to assess the prevalence of GP in the Malay population in relation to gender and age. Methods: The GP of 100 patients were determined using the Probe test method. Other clinical parameters were assessed include crown width/crown length (CW/CL) ratio, tooth morphology and width of keratinised tissue. Periodontal parameters were assessed by two calibrated examiners. Data were analysed using descriptive statistics, one-way ANOVA and Kruskal-Wallis test. Results: A higher prevalence of thick GP was found at the maxilla for both genders, whereas a thin phenotype was observed at the mandible. At maxilla, both thick and thin GP were found in all age groups, while the mandible showed a higher prevalence of thin GP. Significant differences in GP were found between males and females for mandibular and maxillary anterior teeth and the mandibular lateral incisor (p<0.05), while no significant difference was found for other parameters assessed; age group, CW/CL, tooth morphology and WKT. Conclusion: Thicker GP is more prevalent in male population and at maxillary anterior. Mandibular anterior GP presented commonly with a thin GP regardless of gender or age-group. REFERENCES Jepsen S, Caton JG, Albandar JM, Bissada NF, Bouchard P, Cortellini P, Demirel K, de Sanctis M, Ercoli C, Fan J, Geurs NC, Hughes FJ, Jin L, Kantarci A, Lalla E, Madianos PN, Matthews D, McGuire MK, Mills MP, Preshaw PM, Reynolds MA, Sculean A, Susin C, West NX, Yamazaki K. Periodontal manifestations of systemic diseases and developmental and acquired conditions: Consensus report of workgroup 3 of the 2017 World Workshop on the Classification of Periodontal and Peri-Implant Diseases and Conditions. Journal of Clinical Periodontology. 2018; 20: S219-29. https://doi.org/1002/JPER.17-0733 [<a href="https://scholar.google.com/scholar_lookup?title=Periodontal+manifestations+of+systemic+diseases+and+developmental+and+acquired+conditions%3A+Consensus+report+of+workgroup+3+of+the+2017+World+Workshop+on+the+Classification+of+Periodontal+and+Peri-Implant+Diseases+and+Conditions&btnG=">Google Scholar][Pubmed] Kan JY, Morimoto T, Rungcharassaeng K, Roe P, Smith DH. Gingival biotype assessment in the esthetic zone: visual versus direct measurement. International Journal of Periodontics Restorative Dentistry. 2010; 30:237-43.[Google Scholar][Pubmed] Ana SJ, Laurindo ZF, Alberto C. Gingival recession: Its causes and types, and the importance of orthodontic treatment. Dental Press Journal of Orthodontics. 2016; 21(3):18-29. https://doi.org/10.1590/2177-6709.21.3.018-029.oin [Google Scholar] [PMC free article] [Pubmed] Hassan A, Fatin A. Periodontium biotype modification prior to an orthodontic therapy: Case report. King Saud University Journal of Dental Sciences. 2013; 4:91-4. https://doi.org/10.1016/j.ksujds.2013.04.002 [Google Scholar][Crossref] Claffey N, Shanley D. Relationship of gingival thickness and bleeding to loss of probing attachement in shallow sites following nonsurgical periodontal therapy. Journal of Clinical Periodontology. 1986;13(7):654-7. https://doi.org/10.1111/j.1600-051x.1986.tb00861.x [Google Scholar] [Pubmed] Chen ST, Darby IB, Reynolds EC, Clement JG (2009). Immediate implant placement postextraction without flap elevation. Journal of Periodontology. 2009;80:163-72. https://doi.org/10.1902/jop.2009.080243 [Google Scholar][Pubmed] Cosyn J, Hooghe N, De Bruyn H. A systematic review on the frequency of advanced recession following single immediate implant treatment. Journal of Clinical Periodontology. 2012;39:582–9. https://doi.org/1111/j.1600-051X.2012.01888.x [Google Scholar][Pubmed] Abraham SKT, Deepak R, Ambili C, Preeja V, Archana. Gingiva biotype and its clinical significance – A review . The Saudi Journal for Dental Research. 2014;5:3-7. https://doi.org/10.1016/j.ksujds.2013.06.003 [Google Scholar] Cuny-Houchmand M, Renaudin S, Leroul M, Planche M, Guehennec L L, Soueidan A. Gingival biotype: The probe test utility. 2013;3(2):123-7. https://doi.org/10.4236/ojst.2013.32023. [Google Scholar] Singh S, Vandana KL. Assessment of width of attached gingiva in primary, mixed, and permanent dentition: Part - 2. SRM J Res Dent Sci 2017;8:157-61 https://www.srmjrds.in/text.asp?2017/8/4/157/220807 [Google Scholar] De Rouck T, Eghbali R, Collys K, De Bruyn H, Cosyn J. The gingival biotype revisited: transparency of the periodontal probe through the gingival margin as a method to discriminate thin from thick gingiva. Journal of Clinical Periodontology. 2009;36(5):428-33. http://dx.doi.org/10.1111/j.1600-051x.2009.01398.x [<a href="https://scholar.google.com/scholar_lookup?title=The+gingival+biotype+revisited%3A+transparency+of+the+periodontal+probe+through+the+gingival+margin+as+a+method+to+discriminate+thin+from+thick+gingiva&btnG=">Google Scholar][Pubmed] Seibert JL, Lindhe J. Esthetics and periodontal therapy: Textbook of Clinical Periodontology. In: Lindhe J, editor. Copenhangen, Denmark: Munksgaard; 1989. Weisgold AS. Contours of the full crown restoration. Alpha Omegan. 1977; 70:77-8 [Pubmed] Eghbali A, De Rouck T, De Bruyn H, & Cosyn J. The gingival biotype assessed by experienced and inexperienced clinicians. Journal of Clinical Periodontology. 2009; 36:958-63. https://doi.org/10.1111/j.1600-051X.2009.01479.x [Google Scholar][Pubmed] Eger T, Muller HP, Heinecke A. Ultrasonic determination of gingival thickness. Subject variation and influence of tooth type and clinical features. Journal of Clinical Periodontology. 1996;23:839-45. https://doi.org/10.1111/j.1600-051x.1996.tb00621.x [Google Scholar][Pubmed] Muller HP, Schaller N, Eger T, Heinecke A. Thickness of masticatory mucosa. Journal of Clinical Periodontology. 2000; 27:431-6. https://doi.org/10.1034/j.1600-051x.2000.027006431.x [Google Scholar][Pubmed] Barriviera M, Duarte WR, Januario AL, Faber J, Bezerra AC. A new method to assess and measure palatal masticatory mucosa by cone-beam computerised tomoghraphy. Journal of Clinical Periodontology. 2009;36(7):564-8. https://doi.org/10.1111/j.1600-051X.2009.01422.x [Google Scholar][Pubmed] Vandana KL, Savitha B. Thickness of gingiva in association with age, gender, and dental arch location. Journal of Clinical Periodontol. 2005; 32:828-30. https://doi.org/10.1111/j.1600-051X.2005.00757.x [Google Scholar][Pubmed] Shiva Manjunath RG, Anju Rana, Arijit Sarkar. Gingival biotype assessment in a healthy periodontium: Transgingival Probing Method. Journal of Clinical and Diagnostic Research. 2015; 9(5):ZC66-ZC69. https://doi.org/10.7860/JCDR/2015/13759.5956 [Google Scholar][Pubmed] Agarwal, V. Sunny. Mehrotra, N. Vijey, V. Gingival biotype assessment: Variations in gingival thickness with regard to age, gender, and arch location. Indian Journal of Dental Sciences. 2017; 9(1):12-5. https://doi.org/10.4103/0976-4003.201639. [Google Scholar] Rashid R, Ayoub W U. Prevalence of gingival biotype in accordance with age and gender in Kashmiri population. International Journal of Applied Dental Sciences. 2017;3(4):111-13 [Google Scholar] Olsson M, Lindhe J, Marinello CP. On the relationship between crown form and clinical features of the gingiva in adolescents. Journal of Clinical Periodontology. 1993; 20(8):570-77. https://doi.org/ 10.1111/j.1600-051x.1993.tb00773.x [Google Scholar][Pubmed] Seo H, Chung C, Lim S, Hong K. Radiographic evaluation of alveolar bone profile of maxillary anterior teeth in korean young adult. J Korean Acad Periodontol 2006;36:461-71. [Google Scholar] Lang N, Loe H. The relationship between the width of keratinised gingiva and gingiva health. Journal of Periodontology. 1972; 43(10):623-7. https://doi.org/10.1902/jop.1972.43.10.623 [Google Scholar][Pubmed]